Manta ray tourism: interpersonal and social values conflicts, sanctions, and management. Issue 10 (3rd October 2017) - Needham, Mark D.; Szuster, Brian W.; Mora, Camilo; Lesar, Laura; Anders, Emma
ABSTRACT: Scuba diving and snorkeling with manta rays ( M. birostris, M. alfredi ) at sites in Hawaii, USA, have become popular, with upward of 30 tour boats and 300 participants daily. This article examined whether conflicts are occurring within and between these activities and if so, what types of conflict are prevalent and how would participants respond (support restrictions, sanction others). Data from surveys of 444 participants following evening trips to view manta rays showed that 79% of snorkelers experienced in-group conflict with other snorkelers, and 53% of scuba divers reported conflict with other divers. Most conflicts were interpersonal (physical interactions among individuals interfering with experiences). Conflict behaviors included bumping into people (up to 92%), not being aware (up to 73%), and blinding people with underwater flashlights (up to 56%). There were fewer out-group conflicts between different activities (snorkelers vs. scuba divers) and minimal social values conflicts (negative preconceptions, no physical interactions among individuals). Participants supported limiting numbers of snorkelers, scuba divers, and boats, and providing education on how to behave with others. Those experiencing conflicts were more supportive of these strategies and more likely to directly sanction participants causing conflicts, but were not more likely to indirectly sanction managers and operators.